Progress in the understanding of the etiology and predictability of fetal growth restriction. Issue 6 (June 2017) - Tang, Li; He, Guolin; Liu, Xinghui; Xu, Wenming
Abstract : Fetal growth restriction (FGR) is defined as the failure of fetus to reach its growth potential for various reasons, leading to multiple perinatal complications and adult diseases of fetal origins. Shallow extravillous trophoblast (EVT) invasion-induced placental insufficiency and placental dysfunction are considered the main reasons for idiopathic FGR. In this review, first we discuss the major characteristics of anti-angiogenic state and the pro-inflammatory bias in FGR. We then elaborate major abnormalities in placental insufficiency at molecular levels, including the interaction between decidual leukocytes and EVT, alteration of miRNA expression and imprinted gene expression pattern in FGR. Finally, we review current animal models used in FGR, an experimental intervention based on animal models and the progress of predictive biomarker studies in FGR. Free Chinese abstract: A Chinese translation of this abstract is freely available athttp://www.reproduction-online.org/content/153/6/R227/suppl/DC1 .